Avaliação da autoestima de idosas usuárias ou não de cosméticos anti-idade com o uso da Escala Rosember - Julio, Silvana Santoro (2013)
Concerning the growth of elderly population, a new Brazilian demographic reality demands studies in different fields to understand the complexity of this phenomenon. Issues regarding to self-esteem, beauty, vanity and appearance care in this age group might contribute to learn more about aging. This study aimed to assess self-esteem of elderly women, users or non-users of anti-aging cosmetics. The research was conducted within a group of one hundred elder women who belong to a group of elderly people supported by the City of Chapecó-SC. Rosemberg Self-Esteem Scale was used to evaluate the existence between selfesteem and the use of anti-aging cosmetics. Findings show that this aesthetic resource does not influence self-esteem in this sample and therefore Rosemberg Scale might not be appropriate to research with elderly people